Genome Sequencing and Comparative Analysis of Three Hanseniaspora uvarum Indigenous Wine Strains Reveal Remarkable Biotechnological Potential - Guaragnella, Nicoletta; Chiara, Matteo; Capece, Angela; Romano, Patrizia; Pietrafesa, Rocchina; Siesto, Gabriella; Manzari, Caterina; Pesole, Graziano (Frontiers in Microbiology, 2020)
The actual trend in winemaking has highlighted the beneficial contribution of non-Saccharomyces yeasts to wine quality. Hanseniaspora uvarum is one of the more represented non-Saccharomyces species onto grape berries and plays a critical role in influencing the wine sensory profile, in terms of complexity and organoleptic richness. In this work we analyzed a group of H.uvarum indigenous wine strains as for genetic as for technological traits, such as resistance to SO2 and β-glucosidase activity. Three strains were selected for genome sequencing, assembly and comparative genomic analyses at species and genus level. Hanseniaspora genomes appeared compact and contained a moderate number of genes, while rarefaction analyses suggested an open accessory genome, reflecting a rather incomplete representation of the Hanseniaspora gene pool in the currently available genomes. The analyses of patterns of functional annotation in the three indigenous H. uvarum strains showed distinct enrichment for several PFAM protein domains. In particular, for certain traits, such as flocculation related protein domains, the genetic prediction correlated with relative flocculation phenotypes at lab scale. These data contribute to increase the catalog of publicly available genomes from H. uvarum strains isolated from natural grape samples and provides a good roadmap for unraveling the biodiversity and the biotechnological potential of these non-Saccharomyces yeasts.